The Concept of Political Difference in Oliver Marchart and its Relationship with the Heideggerian Concept of Ontological Difference - Efthimiou, Christoforos (Conatus - Journal of Philosophy, 2019)
The concept of political difference concerns the distinction between politics and the political. The political refers to the ontological making possible of the different domains of society, including the domain of politics in the narrow sense. Political difference was introduced as a reaction to the theoretical controversy between foundationalism and anti-foundationalism. This reaction took the form of post-foundationalism. According to Marchart, post-foundationalism does not entirely deny the possibility of grounding. It denies only the possibility of an ultimate transcendent foundation insofar as this ontological impossibility makes possible the historical and contingent grounds in plural. The Heideggerian concept of ontological difference also undermines the possibility of an ultimate ontical ground which establishes the presence of all the other beings. If one wants to think beyond the concept of ground, one should obtain a clear understanding of Being as Being, namely one should grasp the Being in its difference from beings. All the same, Heidegger tends to replace the ontical grounds of metaphysics with Being itself as a new kind of ultimate ontological foundation. On the other hand, one can detect in many points of Heideggerian argumentation traces of a second alternative understanding of ontological difference which does not belong in Heidegger’s intentions and which undermines the primordiality of Being. This alternative understanding establishes a reciprocity between Being and beings. In our view, political difference not only is based in this second way of understanding but, at the same time, develops more decisively the mutual interdependence between Being and beings. In political difference the grounding part, namely the political, possesses both a grounding character and a derivative one. Politics and political both grounds and dislocate each other in an incessant and oscillating, historical procedure which undermines any form of completion of the social.